Dual compensation method for vertical shortening and differential shortening control in high-rise buildings. (1st October 2022) - Wu, Jie; Pang, Cunjun; Dong, Baiping
Abstract: This paper presents a dual compensation (DC) method to compensate the shortenings of vertical members and control the differential shortenings between vertical members in high-rise buildings. Resulting from different material properties, load distributions, time-dependent shrinkage and creep effects, and other factors, the shortenings of vertical members and the associated differential shortenings can be substantial in high-rise buildings, which could cause damages in structural and nonstructural components. In this paper, to ensure the floor elevations of a built high-rise building be consistent with the design elevations, the floor elevation control method is used to simplify and increase the efficiency of the conventional optimal compensation (OC) method for differential shortening control. Based on the simplified OC (SOC) method, the DC method, which provides specific length correction values for specific types of vertical members such as columns and core walls, is formulated to accurately control the differential shortenings between various types of vertical members. Compared to the OC method, the DC method can be easily executed during the construction process and it does not compromise story height reduction for differential shortening control. The performance of both the SOC method and DC method in differential shortening control are compared to that of the OC method in a 70-story verifying building, and demonstrated in a 117-story building as well. The results demonstrated that the DC method can effectively compensate the shortenings of vertical members and control the differential shortenings between vertical members in high-rise buildings. Highlights: A dual compensation method for differential shortening control is proposed. The existing optimal compensation method is improved. Dual compensation method can provide specific correction values for various members. The effectiveness and efficiency of the dual compensation method are validated. The dual compensation method is successfully applied in a 117-story building.